Proceedings of the 3rd International Conference on Economics, Business and Economic Education Science, ICE-BEES 2020, 22-23 Jul 2021
DOI: 10.4108/eai.22-7-2020.2307872
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Implementing Sukuk for Infrastructure Financing in Indonesia Using the Analytic Network Process

Abstract: The Indonesian government has used sukuk to finance infrastructure since 2013. However, the issuance of sukuk for infrastructure financing is still low compared to the total value of available underlying assets because of many problems and barriers. This study aims to identify priority problems, solutions and strategies in the implementation of sukuk for infrastructure financing from the obligor perspective. The research uses analytic network process method. The results show that the priority of the problem is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Finally, market risk depends on the rate of return. The Sukuk that fixes the yield will reduce the income of the sukuk when there is an increase market returns (Fauziah et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, market risk depends on the rate of return. The Sukuk that fixes the yield will reduce the income of the sukuk when there is an increase market returns (Fauziah et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings show that there is a potential additional cost of debt because of hindrance in project implementation. In addition, the gap between implementation and planning reflects the weakness of the SBSN Project (Fauziah et al, 2021a(Fauziah et al, , 2021b. The latter was concluded by Aziza and Yaumbi (2020), who found that there is a potential loss of quality in state-owned assets in the event of negligence by parties in the settlement.…”
Section: Previous Studiesmentioning
confidence: 99%
“…19 Year 2008, which is for state budget deficit and government project financing. Other research on Sovereign Sukuk evaluation mainly assesses the acceptance of investors (Fauziah et al , 2021a; Muchtar, 2021), Sharia law compliance (Adeagbo, 2021; Ahmed et al , 2019; Noordin et al , 2018), the performance of Sukuk as an investment instrument in the bond market (Bella et al , 2021; Solihat et al , 2020; Sukmana, 2020; Tülgen Çetin and Metlek, 2021) and the extended proposal for Sukuk fund utilisation (Al-Suwailem, 2021; Anindito Mujizat, 2021; Fauziah et al , 2021b; Handayani and Surachman, 2017; Hariyanto, 2020; Mawardi et al , 2021; Pribadi, 2020; Rusydiana and Irfany, 2021). None of the extant research discusses the effectiveness of Sukuk in financing government projects or evaluates the mechanism of Sukuk fund disbursement.…”
Section: Introductionmentioning
confidence: 99%